PENGARUH PENAMBAHAN TEPUNG BUNGA ROSELLA (Hibiscus sabdariffa L.) SEBAGAI FEED ADDITIVE TERHADAP KUALITAS FISIK DAN SENSORIS DAGING AYAM BROILER - , DEVI HENDHILA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study was designed to investigate the physical and sensory quality of broiler meat those their feed added with rosella (Hibiscus sabdariffa L.) as a feed additive. This study was using 72 birds of broiler, Lohman strain, those divided into 6 groups of treatment with each treatment consisted of three replications and each replication was using 4 birds of broiler. Treatments additive were 0.00